Description of eight new Phaoniinae species from the Ethiopian region (Diptera: Muscidae). - Zielke, Eberhard (Contributions to Entomology = Beiträge zur Entomologie, 1971)
Eight new species of the genera Limnophora, Hennigmyia, Hydrotaea, Helina and Mydaea from the Ethiopian region are described and compared with related species. Nomenclatural Actsparacaesioides Zielke, 1971 (Helina), spec. n.patersoni Zielke, 1971 (Helina), spec. n.zumpti Zielke, 1971 (Hennigmyia), spec. n.tanzaniae Zielke, 1971 (Hydrotaea), spec. n.wittei Zielke, 1971 (Hydrotaea), spec. n.abdominalis Zielke, 1971 (Limnophora), spec. n.stuckenbergi Zielke, 1971 (Limnophora), spec. n.capensis Zielke, 1971 (Mydaea), spec. n.